Advanced Transmission Electron Microscopy for Electrode and Solid‐Electrolyte Materials in Lithium‐Ion Batteries. Issue 8 (3rd June 2018) - Liu, Xiaozhi; Gu, Lin
Abstract: Understanding the reaction processes of electrode and electrolyte materials is important for achieving high‐performance lithium‐ion batteries (LIBs). Currently, transmission electron microscopy (TEM) and scanning transmission electron microscopy (STEM) can readily characterize the structural and chemical features of these materials from the micrometer scale to the atomic scale. In situ (S)TEM can further monitor their non‐ or quasi‐equilibrated states in real time. Here, the recent progress in unraveling the crystal and electronic structures of the electrode and solid‐electrolyte materials using ex situ and in situ (S)TEM is reviewed. Three fundamental functions, including imaging, diffraction, and spectroscopy, are jointly used to decipher the configuration of the defects and ordering, the variations near the surfaces and across the interfaces, and the evolution of the coexisting phases. Novel and deep insights are proposed for the material growth, reaction, and capacity fading mechanisms. Advanced (S)TEM studies for LIB materials pose numerous challenges and perspectives, including the development and application of local diffraction analysis, large‐scale phase mapping techniques, 3D reconstruction, and cryoelectron microscopy, which are further discussed. Abstract : Transmission electron microscopy (TEM) has three basic functions, including diffraction, imaging, and spectrometry. Both ex situ and in situ TEM have advanced to provide fruitful insights into the chemistry and structural dynamics of electrode and electrolyte materials. Understanding of the structure–property relationships under different working conditions has evolved to the atomic scale.